2007
DOI: 10.1007/s00440-007-0083-0
|View full text |Cite
|
Sign up to set email alerts
|

Infinite volume limit of the Abelian sandpile model in dimensions d ≥  3

Abstract: Abstract:We study the Abelian sandpile model on Z d . In d ≥ 3 we prove existence of the infinite volume addition operator, almost surely with respect to the infinite volume limit µ of the uniform measures on recurrent configurations. We prove the existence of a Markov process with stationary measure µ, and study ergodic properties of this process. The main techniques we use are a connection between the statistics of waves and uniform two-component spanning trees and results on the uniform spanning forest meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 23 publications
0
43
0
Order By: Relevance
“…From the definition of topological entropy we obtain that 13) which completes the proof of the theorem. L the equidistributed probability measure on the set S…”
Section: Surjectivity Of the Maps ξmentioning
confidence: 56%
See 1 more Smart Citation
“…From the definition of topological entropy we obtain that 13) which completes the proof of the theorem. L the equidistributed probability measure on the set S…”
Section: Surjectivity Of the Maps ξmentioning
confidence: 56%
“…1 In [10], Dhar showed that the topological entropy of the shift-action σ R ∞ on R ∞ is also given by (3.4), which implies that every shift-invariant measure µ of maximal entropy on R ∞ has entropy (1.1). Shift-invariant measures on R ∞ were studied in some detail by Athreya and Jarai in [1,2], Jarai and Redig in [13]; however, the question of uniqueness of the measure of maximal entropy is still unresolved. Spanning trees of finite graphs are classical objects in combinatorics and graph theory.…”
Section: Introductionmentioning
confidence: 99%
“…The following immediate corollary will be useful in controlling avalanches. A version of part (i) was proved in [15,Lemma 7.5].…”
Section: Intermediate Configurationsmentioning
confidence: 97%
“…All our results have analogues in large finite V (L), or indeed are derived therefrom. Passing to the limit of Z d is not too difficult when d ≥ 3, due to the result of Járai and Redig [15,Theorem 3.11] showing that ν(|S| < ∞) = 1. When d = 2, this is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Járai and Redig [39] showed that the burning bijection allows one to relate avalanches to the past of the WUSF, which allowed them to prove that avalanches in Z d satisfy P(v ∈ AvC 0 (H)) v −d+2 for d ≥ 5. (The fact that the expected number of times v topples scales this way is an immediate consequence of Dhar's formula, see [38, Section 3.3.1].)…”
Section: Applications To the Abelian Sandpile Modelmentioning
confidence: 99%